Remote coaching for supporting the implementation of treatment for depression in primary care in Madhya Pradesh, India: protocol for a cluster randomized controlled trial - Bondre, Ameya P.; Singh, Abhishek; Tugnawat, Deepak; Chandke, Dinesh; Khan, Azaz; Shrivastava, Ritu; Lu, Chunling; Ramaswamy, Rohit; Patel, Vikram; Bhan, Anant; Naslund, John A. (Frontiers in Health Services, 2024)
BackgroundUpwards of ninety percent of individuals living with depression in India do not have access to evidence-based treatments, especially in rural areas. Integrating these treatments into primary care is essential for bridging this care gap. This trial aims to evaluate whether a remote coaching implementation support strategy, referred to as Enhanced Implementation Support, is superior to routine support, referred to as Routine Implementation Support, in supporting the delivery of collaborative depression care in rural primary care centers.MethodsEmploying a cluster-randomized hybrid type-III implementation trial design, 14 primary care facilities in Sehore district, Madhya Pradesh, will implement a collaborative depression care package based on the WHO's mhGAP program. Facilities will be randomized to either Enhanced Implementation Support or the Routine Implementation Support control condition. Enhanced Implementation Support consists of remote coaching and technical assistance, supplemented with in-person visits, and guided by the Plan-Do-Study-Act implementation cycles. The primary implementation outcome is the proportion of outpatients screened for depression by facility staff, with secondary outcomes including the proportions of outpatients who screen positive for depression, are referred to the medical officer, and initiate treatment. Secondary patient outcomes include proportion of patients who achieve reduction in depression symptom severity at 3-month follow up. Acceptability, feasibility, and fidelity of the depression care package will be assessed through routine observations collected during field visits, facility audits, and qualitative exit interviews with facility staff. Costs of delivering the Enhanced Implementation Support strategy will also be estimated.DiscussionThis trial can inform efforts to integrate depression care in rural primary care facilities in a low-resource setting, and illuminate whether external coaching support is superior relative to existing implementation support for achieving these goals. Trial RegistrationNCT05264792.